2016
DOI: 10.1021/acs.jafc.6b00425
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic Activity of Ethanol Extracts of Arctium lappa L. Undried Roots and Its Active Compound, Oleamide, in Regulating FcεRI-Mediated and MAPK Signaling in RBL-2H3 Cells

Abstract: The antiallergic potential of Arctium lappa L. was investigated in Sprague-Dawley rats, ICR mice, and RBL-2H3 cells. Ethanol extract (90%) of A. lappa (ALE, 100 μg/mL) inhibited the degranulation rate by 52.9%, determined by the level of β-hexosaminidase. ALE suppressed passive cutaneous anaphylaxis (PCA) in rats and attenuated anaphylaxis and histamine release in mice. To identify the active compound of ALE, we subsequently fractionated and determined the level of β-hexosaminidase in all subfractions. Oleamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…In the last part of this study, oleamide and a plastic syringe extract, which showed to contain oleamide, appeared to interfere with the current (inflammatory) bioassay as they exhibited activity. Several biological studies have already reported anti-inflammatory activity of oleamide [9][10][11][12][13] in concentration of 100 μg mL −1 12 . In our employed bioassay system, oleamide showed small but significant (p < 0.001) anti-inflammatory activity in high doses (100 μg mL −1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last part of this study, oleamide and a plastic syringe extract, which showed to contain oleamide, appeared to interfere with the current (inflammatory) bioassay as they exhibited activity. Several biological studies have already reported anti-inflammatory activity of oleamide [9][10][11][12][13] in concentration of 100 μg mL −1 12 . In our employed bioassay system, oleamide showed small but significant (p < 0.001) anti-inflammatory activity in high doses (100 μg mL −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various other pharmacological effects of oleamide such as cannabinoid like behaviour 6,14 , inhibition of the enzyme human monoamine oxidase B 8,15 , closure of gap-junctions 16 and activation of TRPV1 vanilloid receptors 16 are also communicated. Despite the already reported studies regarding bioassay interferences 8,15,17 from plastic labware leachables, including oleamide, it has been continuously reported as analyte in natural extracts 5,11,12,[18][19][20][21] . At the same time, it has been rarely double checked to be a possible plastic labware interference 22-25 , perhaps due to its natural origin.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Bioassay-guided fractionation is a well-established approach for untargeted, but focused screening of active compounds in complex matrices. [44][45][46][47][48] From the identified compounds (Table S2 †), p-cymene, cinnamyl alcohol, cinnamic acid and cinnamalde-hyde are present in Cinnamomum verum extract, with the latter as major active principle. 15,24,49,50 To the best of our knowledge, the other compounds shown in Table S2 † were not reported to be present in cinnamon extract so far.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol extract (90%) of AL (ALE, 100 µg/mL) inhibited the degranulation rate by 52.9%, determined by the level of β-hexosaminidase. ALE suppressed PCA in rats and attenuated anaphylaxis and histamine release in mice [68].…”
Section: Anti-ulcerogenic Activitymentioning
confidence: 89%